2022
DOI: 10.1002/admi.202102072
|View full text |Cite
|
Sign up to set email alerts
|

Optical and Structural Properties of Insoluble and Flexible Biodegradable Regenerated Silk Films for Optically Transparent Hydrophilic Coating of Medical Devices

Abstract: materials have been identified as one of the promising materials for use in transparent devices such as optoelectronic devices, photovoltaic cells, and medical devices. [2] Numerous medical devices, such as tubes, catheter, mechanical heart valves, lenses, and disposable plastic slides, require enhanced wettability in order to function properly with physiological fluids and tissues. [3] For the fabrication of medical devices that come into contact with blood and tissue, it is usually desirable to utilize mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 35 publications
0
0
0
Order By: Relevance
“…As of our current knowledge, there is a notable absence of dedicated studies examining the impact of different sugar alcohol plasticizers on the properties of silk fibroin coatings. Previous research has well established that β-sheet crystallites significantly influence the properties of silk fibroin materials 12 Numerous researchers have employed FTIR to investigate the conformation transition kinetics from random coil and/or helix to β-sheet in silk proteins when exposed to various solvents, including methanol, ethanol, propanol, and isopropanol 1 , 12 14 In our previous study 15 , it was demonstrated that alcohol treatment reduced the β-sheet content in silk fibroin films. However, in this current study, it is expected that treatment with sugar alcohols will enhance the crystallization of the films, thereby increasing the β-sheet content.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…As of our current knowledge, there is a notable absence of dedicated studies examining the impact of different sugar alcohol plasticizers on the properties of silk fibroin coatings. Previous research has well established that β-sheet crystallites significantly influence the properties of silk fibroin materials 12 Numerous researchers have employed FTIR to investigate the conformation transition kinetics from random coil and/or helix to β-sheet in silk proteins when exposed to various solvents, including methanol, ethanol, propanol, and isopropanol 1 , 12 14 In our previous study 15 , it was demonstrated that alcohol treatment reduced the β-sheet content in silk fibroin films. However, in this current study, it is expected that treatment with sugar alcohols will enhance the crystallization of the films, thereby increasing the β-sheet content.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrophilic coatings are acknowledged for their ability to render medical devices wettable while minimizing surface friction. Amongst these materials, our prior study has demonstrated that modified regenerated silk fibroin (SF) stands out as a promising choice for hydrophilic coating applications 1 . This is attributed to its remarkable characteristics, including high biocompatibility, excellent biodegradability, and its absence of immunogenicity and allergenicity.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations